Evolving trends in oral cancer burden in Europe: a systematic review - Amr Sayed Ghanem; Hafsa Aijaz Memon; Attila Csaba Nagy (Frontiers in Oncology, 2024)
IntroductionOral cavity cancer (OCC), primarily oral squamous cell carcinoma (OSCC), is a growing concern in Europe, particularly among younger populations. Preventable lifestyle factors and social determinants of health contribute significantly to the disease burden. Limited access to healthcare and delayed diagnoses further complicate treatment and reduce survival rates.MethodsThis systematic literature review adhered to PRISMA guidelines to explore trends in OSCC epidemiology, etiology, diagnosis, treatment, and survival across Europe. A comprehensive search strategy using PubMed, GLOBOCAN data, and the EUROCARE-5 study identified relevant articles focusing on human populations in Europe with a primary interest in OSCC epidemiology. Only peer-reviewed publications in English with full-text access were included.ResultsThis study investigated the burden of OSCC across Europe, revealing variations in incidence, mortality, and prognosis. Eastern and Central Europe displayed the highest burden. Males exhibited a significantly higher risk compared to females. Age-related disparities existed in life expectancy and time to achieve favorable outcomes. HPV emerged as a growing risk factor for oropharyngeal cancer. Public health strategies should target modifiable risk factors and improve early detection.ConclusionThis review reveals concerning disparities in European OSCC. Region, sex, and age all influence burden and prognosis. Future research should focus on controlling risk factors and personalized medicine to optimize treatment. This will lead to a Europe with reduced OSCC incidence and demonstrably better patient outcomes.